2021
DOI: 10.1002/ecs2.3445
|View full text |Cite|
|
Sign up to set email alerts
|

Recovery of the herbaceous component of degraded sagebrush steppe is unimpeded by 75 years of moderate cattle grazing

Abstract: Understanding the effects of contemporary cattle grazing on herbaceous perennial communities in big sagebrush steppe is important for managing for wildlife habitat, plant diversity, and productivity, yet potentially complicated by legacy impacts of historic, often higher intensity, livestock grazing. Here, we evaluate whether recovery of herbaceous communities in eastern Oregon, USA, after the cessation of intense spring sheep grazing (1935) was affected by moderate cattle grazing in paired plots with or witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 70 publications
(99 reference statements)
2
18
0
Order By: Relevance
“…In some studies, heavy grazing intensities have been shown to homogenize vegetation through selective pressure (Adler & Lauenroth, 2000; Adler et al, 2001; Anderson & Briske, 1995), and we expected that we would find greater similarity in species composition between plots at the heavily grazed end of our gradient. However, other grazing studies in semiarid rangelands have reported small or no effects of grazing on species composition, consistent with our study (Copeland et al, 2021; Courtois et al, 2004; Davies et al, 2016; Fernandez‐Gimenez & Allen‐Diaz, 2001). In addition, a global meta‐analysis of grazing effects on plant community composition showed little difference in composition when grazing pressure switched from moderate to low levels or even to no grazing (Herrero‐Jáuregui & Oesterheld, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In some studies, heavy grazing intensities have been shown to homogenize vegetation through selective pressure (Adler & Lauenroth, 2000; Adler et al, 2001; Anderson & Briske, 1995), and we expected that we would find greater similarity in species composition between plots at the heavily grazed end of our gradient. However, other grazing studies in semiarid rangelands have reported small or no effects of grazing on species composition, consistent with our study (Copeland et al, 2021; Courtois et al, 2004; Davies et al, 2016; Fernandez‐Gimenez & Allen‐Diaz, 2001). In addition, a global meta‐analysis of grazing effects on plant community composition showed little difference in composition when grazing pressure switched from moderate to low levels or even to no grazing (Herrero‐Jáuregui & Oesterheld, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Livestock grazing did not dramatically alter plant community structure of the big sagebrush stands we sampled. Cattle grazing can modify dryland plant community structure (Davies et al, 2018; Eldridge et al, 2016; Veblen et al, 2015), but over the range of big sagebrush there is varying sensitivity to modern grazing practices, which are likely to be driven by the interactions of climate, historical grazing pressure, and modern plant community composition (Copeland et al, 2021; Davies et al, 2018). Collectively, our findings support existing evidence that the balance between grasses and shrubs in big sagebrush ecosystems is relatively stable with current grazing practices (Davies et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of the relatively strong evidence that inappropriate grazing has contributed to less perennial herbs and more exotic annual grasses (Pyke et al, 2016), findings from grazing exclosures have provided mixed evidence for grazing impacts, even though these studies are expected to provide the strongest inference owing to their greater experimental control of confounding factors (Davies et al, 2009, 2021; Davies, Bates, & Boyd, 2016; Davies, Bates, Boyd, & Svejcar, 2016; Porensky et al, 2020; Veblen et al, 2015; Yeo, 2005). The difference in correlative compared to exclosure‐experiment findings may relate to a tendency of grazing‐exclosure studies in sagebrush steppe to be located in areas in relatively good ecological condition and/or relatively low abundances of cheatgrass (Anderson & Inouye, 2001; Condon et al, 2020; Copeland et al, 2021; Courtois et al, 2004; Davies et al, 2012, 2018; Davies, Bates, & Boyd, 2016; Davies, Bates, Boyd, & Svejcar, 2016; Porensky et al, 2020). Assessments of whole‐community responses to grazing exclusion in the presence of invasive threats are thus needed.…”
Section: Introductionmentioning
confidence: 99%